Mutagenicity of Mouriri pusa Gardner and Mouriri elliptica Martius - Santos, F. V. [UNESP]; Tubaldini, F. R. [UNESP]; Colus, I. M. S.; Andreo, M. A.; Bauab, Taís Maria [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Mouriri pusa Gardner and Mouriri elliptica Martius are fruit-bearing plants of the Melastomataceae family, popularly known in Brazil as puca-preto or jaboticaba-do-cerrado, and they are used in folk medicine for the treatment of gastric ulcers. In this study, we employ the Ames test to assess the mutagenicity of compounds obtained from the leaves of these species. The methanol extract of the M. pusa was mutagenic to the Salmonella typhimurium strains TA98, TA97a and TA100, with or without metabolic activation. The methanol extract of M. elliptica induced mutagenic activity in TA98 when metabolized with S9 fraction and TA97a with and without S9, but with lower mutagenicity index (MI) and potencies values than those for M. pusa. Enriched fractions of flavonoids and tannins of M. pusa were also evaluated and they demonstrated positive mutagenicity. The highest values of MI and potency were obtained with the flavonoid fraction, which contains large amounts of quercetin, quercetin glycosides and myricetin. These compounds are probably related to the mutagenicity observed in the Ames test. The dichloromethane extract was not mutagenic in any of the test conditions employed. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mouriri pusa; Mouriri elliptica; melastomaraceae; mutagenicity; Ames test; medicinal plants